Crop commercialization in Ethiopia: Trends, drivers, and impact on well-being - Minot, Nicholas; Warner, James; Aredo, Samson Dejene; Zewdie, Tadiwos (International Food Policy Research Institute, 2022)
Agricultural transformation refers to a series of changes in agriculture that both reflect and drive rising income and economic development more broadly. While the macroeconomic patterns of agricultural transformation are relatively well documented, less is known about how it is manifested at the household level. Ethiopia makes an excellent case study as it has had one of the fastest growing economies in the world. An important aspect of this process is agricultural commercialization, that is, the rising share of agricultural output is sold on the market rather than being consumed at home. Agricultural commercialization tends to rise with development with improved infrastructure and communications, the availability of inputs and know-how regarding commercial crop production, and farmers being willing to accept the risks associated with producing crops for the market. Agricultural commercialization is widely believed to allow farmers to earn higher income as they specialize in crops for which they have a comparative advantage. The analysis makes use of a data from three rural household surveys carried out in Ethiopia by IFPRI in 2012, 2016, and 2019. Each survey used a sample that was representative of the four main agricultural regions of the country (Tigre, Oromia, Amhara, and SNNP) with sample sizes of 3000 to 5000, including 1,900 households that were interviewed in all three rounds. In addition, we incorporate several weather variables based on CHIRPS rainfall data to estimate the effect of the level and variability of rainfall on agricultural commercialization.